POVERTY REDUCTION POLICY IN THE NATIONAL ECONOMY AND ITS SOCIO-ECONOMIC MECHANISMS (Analysis of International Sciences, 2024)
In order to solve the problems of increasing the standard of living and the quality of life in the country, the concept of eliminating the poverty of the population is necessary for labor. Taking into account the measures clearly defined by the President of the Republic, economists are trying to substantiate this concept and to clarify a number of measures and conditions for the independent release of the working population from poverty based on decent work.